Baseline neutrophil‐to‐lymphocyte ratio predicts response to corticosteroids and is associated with infection and renal dysfunction in alcoholic hepatitis. Issue 4 (17th July 2019) - Forrest, Ewan H.; Storey, Natasha; Sinha, Rohit; Atkinson, Stephen R.; Vergis, Nikhil; Richardson, Paul; Masson, Steven; Ryder, Stephen; Thursz, Mark R.; Allison, Michael; Fraser, Andrew; Austin, Andrew; et al.
Summary: Background: Treating severe alcoholic hepatitis involves the exposure of patients to corticosteroids for 7 days to assess "response". Aim: To assess the prognostic and therapeutic implications of baseline neutrophil‐to‐lymphocyte ratio (NLR) in patients with severe alcoholic hepatitis. Methods: Patients recruited to the STOPAH trial and an independent validation group were analysed retrospectively. Area under the receiver operating curve (AUC) analysis was performed. Kaplan‐Meier analysis was used to assess survival. Log‐rank test and odds ratio (OR) were used for comparative analysis. Results: Baseline NLR was available for 789 STOPAH patients. The AUC for NLR was modest for 90‐day outcome (0.660), but was associated with infection, acute kidney injury (AKI) and severity of alcoholic hepatitis. Ninety‐day survival was not affected by prednisolone treatment if NLR < 5 or > 8 but mortality was reduced with prednisolone treatment when the NLR was 5‐8 (21.0% cf. 34.5%; P  = 0.012). Prednisolone treatment increased the chance of Lille response if the NLR was  ≥ 5 (56.5% cf. 41.1%: P  = 0.01; OR 1.86) but increased the risk of day 7 infection (17.3% cf. 7.4%: P  = 0.006; OR 2.60) and AKI (20.8% cf. 7.0%: P  = 0.008; OR 3.46) if the NLR was > 8. Incorporation of NLR into a modified Glasgow alcoholic hepatitis score (mGAHS) improved the AUC to 0.783 and 0.739 for 28‐day and 90‐day outcome, respectively. Conclusion: The NLR is associated with AKI and infection in severe alcoholic hepatitis. The NLR identifies those most likely to benefit from corticosteroids at baseline (NLR 5‐8). The mGAHS has a good predictive value for 28‐ and 90‐day outcomes. Abstract : Linked Content This article is linked to Abdallah and Singal paper. To view this article, visit https://doi.org/10.1111/apt.15399 .